The Legitimacy of Indigenous Peoples Norms Under International Law by Claire Charters :: SSRN - Charters, Claire (University of Auckland, 2012)
Keywords: UNDRIP; crown; crown policy; indigenous rights; international law; labour party

Te Pītau o te Tuakiri: Affirming Māori Identities and Promoting Wellbeing in State Secondary Schools - Rata, Arama (2012)
Numerous researchers have posited links between ethnic identity and psychological wellbeing (Phinney, 1992; Martinez & Dukes, 1997; Roberts, Phinney, Masse, Chen, Robers, & Romero, 1999; Houkamau & Sibley, 2011), and Māori cultural interventions have been suggested as a means of promoting a range of positive outcomes (e.g. M. Durie, 1998; Durie, 2003b; Lawson-Te Aho, 1998). However, longitudinal evidence of causal pathways between Māori ethnic identity and psychological wellbeing remains scarce, and evidence of the positive impacts of cultural interventions is not well documented. The present thesis investigates Māori identity development in the context of State secondary schools, and explores the relationships between Māori cultural engagement, Māori identity, and psychological wellbeing. A methodology that incorporates both mātauranga Māori (Māori knowledge) and Western scientific knowledge bases and research methods was applied. Interviews were held with Māori students and their whānau (families) at a State secondary school where a community-driven initiative to improve Māori student outcomes took place. Thematic analysis was used to generate Te Korowai Aroha Framework, outlining how Māori cultural initiatives can enable schools to fulfil their duty of care and meet Māori community needs by affirming individuals‟ cultural identity and agency, by building relationships based on mutual respect, and by working collaboratively within the school and with external services providers. Thematic analysis of these interviews was also conducted to generate The Pōwhiri Identity Negotiation Framework. The pōwhiri (formal welcome), in which Māori creation narratives are ritually re-enacted, is used as a metaphor for Māori identity negotiation. The stages of creation Te Kore, Te Pō, Te Whaiao, and Te Ao Marama are used to describe, respectively: those who were yet to display interest in Māori cultural identities; those who were interested in developing their Māori identities; those who were actively exploring their Māori identities; and those who felt secure in their Māori identities. Quantitative longitudinal survey data from over 300 Māori adolescents in the Youth Connectedness Project was then analysed. Structural Equation Modelling revealed that Māori cultural engagement positively predicted Māori ethnic identity, and that Māori ethnic identity positively predicted psychological wellbeing, in support of hypotheses. In addition, Hierarchical Linear Modelling revealed that the higher a school‟s level of Māori cultural promotion, the higher the ethnic identity of its students was likely to be. The results of this thesis demonstrate the impact of school cultural environments on individual identity development, and provide evidence that cultural engagement initiatives can enhance Māori identities, which in turn can increase psychological wellbeing. The results from the studies presented in this thesis are incorporated into Te Pītau o te Tuakiri framework, outlining how Māori identities can be nurtured, and the results are also used to offer guidelines for individuals wishing to become more engaged in Māori culture, and institutions wishing to become more responsive to Māori communities. These findings are used to challenge educators and policy makers to ensure schools and other State institutions support Māori cultural expression and affirm Māori identities.
Keywords: colonisation; education; identity; policy; wellbeing